1980
DOI: 10.1161/01.res.46.4.530
|View full text |Cite
|
Sign up to set email alerts
|

Time course of changes in the mechanical properties of the canine right and left ventricles during hypertrophy caused by pressure overload.

Abstract: We developed a mathematical model of the right and left ventricles to determine whether there is a change in the mechanical properties of muscle during the hypertrophy process resulting from pulmonary arterial banding. Pressure-volume data were obtained from 10 normal dog hearts and 8 dog hearts in which the pulmonary artery was banded for periods of 2--40 weeks. These data were applied to the model, and the time course of wall stress and muscle stiffness was quantified for both ventricles. The results demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 42 publications
(26 reference statements)
2
7
0
Order By: Relevance
“…Prior reports have already recommended that neither ventricular mass nor wall thickness should be used as a substitute for estimating myocardial stiffness, thus corroborating our findings [1, 43, 44]. …”
Section: Discussionsupporting
confidence: 91%
“…Prior reports have already recommended that neither ventricular mass nor wall thickness should be used as a substitute for estimating myocardial stiffness, thus corroborating our findings [1, 43, 44]. …”
Section: Discussionsupporting
confidence: 91%
“…[17][18][19] The relation between average midwall circumferential wall stress and midwall circumferential strain was used to describe the intrinsic compliance of a circumferential myocardial hoop at the equator of the LV. To estimate midwall circumferential stress at the equator of the LV, an effective external LV pressure (ELVP) was calculated with the assumption that two thirds of the surface area of the LV is surrounded by the pleural cavity (since the pericardial incision was loosely approximated) and one third is surrounded by the RV'7 (i.e., ELVP=[2Pp +RV pressure]/3).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that collagen fibres could serve as a transducer regulating myocyte growth and protein synthesis Jalil et al 1989). Moreover, several reports have shown that structural and molecular changes in non-contractile proteins may cause such serious functional alterations of the heart as myocardial stiffness (Mirsky & Laks 1980;Mortz & Struer 1989).…”
Section: Methodsmentioning
confidence: 99%